Characterization and nano-engineering the interface properties of PVA fibers in strain-hardening cementitious composites incorporating high-volume ground-glass pozzolans. (20th February 2020) - Hisseine, Ousmane A.; Tagnit-Hamou, Arezki
Graphical abstract: Highlights: The use of glass powder (GP) increases packing density and frictional bond ( τ 0 ). Too high packing density leads to excessive τ 0 and premature rupture in PVA fibers. Premature fiber rupture reduces composite ductility. Nanocellulose filaments (CF) attenuate τ 0 and impart noticeable slip-hardening ( β ). Improved β by CF increases fiber bridging capacity and composite ductility. Abstract: In the context of enhancing concrete ecoefficiency through the valorization of domestic materials into concrete design, increasing research attention is being paid to the development of strain-hardening cementitious composites (SHCC) with various supplementary cementitious materials (SCM) in replacement of the commonly used fly ash (FA). In this regard, ground-glass pozzolans [or simply glass powder (GP)] obtained by grinding post-consumer waste glass can shape a potential candidate. This study is aimed at characterizing the interface properties of polyvinyl-alcohol (PVA) fibers in SHCC incorporating high-volume GP (HVGP) at 0–100% replacement of FA. Single-fiber pull-out tests were conducted to characterize the interface properties [frictional bond ( τ 0 ), chemical bond ( Gd ), and slip-hardening coefficient ( β )] necessary for micromechanical tailoring of SHCC. Results indicate that with higher matrix compactness obtained using GP, τ 0 increased significantly, while Gd slightly decreased. Whereas higher τ 0 in HVGP-SHCC was found to increase the maximum pull-out load of PVA fibers, excessive τ 0 causes fiber damage, thereby adversely affecting composite ductility. Therefore, a novel approach was adopted herein to nanomodify SHCC matrix as well as fiber/matrix interface by incorporating nanoscale cellulose filaments (CF) at rates of 0.03–0.10% per cement mass. This allowed to significantly alter the pull-out behavior whereby τ 0 and Gd were relatively attenuated, while a significant increase in β ( 1.0–1.5) was obtained. Thus, the incorporation of CF imparted a characteristic slip-hardening effect that contributed towards enhancing the strain-hardening capacity in HVGP-SHCC as experimentally validated by uniaxial tensile tests.